Determination of the Effect of Epigallocatechin Gallate on Oxidative Stress, Apoptosis and Sperm Quality in Rabbit Semen - Akarsu, Serkan Ali; Koca, Recep Hakkı; Cihangiroğlu, Aslıhan Çakır; Acısu, Tutku Can; Güngör, İbrahim Halil; Sönmez, Mustafa; Duruel, Harika Eylül Esmer (Fazile Nur EKİNCİ AKDEMİR, 2023)
Objectives;In this study, it was aimed to determine the effect of Epigallocatechin gallate (EGCG) on the cryopreservation of rabbit semen. Material and metod; For this purpose, semen was collected from six male New Zealand rabbits. Collected semen were divided into 5 groups as control, 25 µM, 50 µM, 100 µM and 200 µM. Semen samples were reconstituted and frozen after adding EGCG. Frozen straws were then thawed. Results; After freezing and thawing, total motility, progressive motility, and rate of fast and medium speed sperm were significantly higher in the 50 µM group than in the other groups. Static sperm ratio was found to be lower in the 50 µM group than in the other groups. When the flow cytometry results were examined, there was no statistical difference between the groups in terms of the ratio of dead and live sperm. However, the rate of dead sperm with acrosome damage was found to be the lowest in the 50 µM group. High mitochondrial membrane potential sperm ratio was found higher in 50 µM and 100 µM groups compared to other groups (p
Keywords: Reproductive Medicine (Other); Üreme Tıbbı (Diğer)